Gregor the Overlander - Collins, Suzanne (New York : Scholastic, 2003)
When eleven-year-old Gregor and his two-year-old sister are pulled into a strange underground world, they trigger an epic battle involving men, bats, rats, cockroaches, and spiders while on a quest foretold by ancient prophecy.
Includes After Words bonus features: interview, information, activities; and a sneak peek at Book Two in the Underland chronicles ([21] p.).
630
Accelerated Reader AR
Keywords: Brothers and sisters -- Juvenile fiction; Animals -- Juvenile fiction; Missing persons -- Juvenile fiction; Young adult fiction; Fantasy fiction